Resistance exercise promotes functional recovery from peripheral nerve injury - Al-Sarraf, Hameed; Al Mallah, Hind; Mouihate, Abdeslam (Frontiers in Physiology, 2025)
Studies on the effect of exercise before peripheral nerve injuries are scarce, with even less attention given to the effects of resistance exercise. In this study, rats were first trained for 10 weeks using a novel resistance exercise system developed in our laboratory, and then they were subjected to either a mild compression or a moderate crush injury of their sciatic nerve. Functional tests, including toe spread reflex, foot positioning, extensor postural thrust, and CatWalk, were carried out at pre- and on selected days post-injury. Animals were sacrificed, and sciatic nerves were collected on the fifth day and the 14th day after the compression and crush-injured rats, respectively. Myelin proteins were analyzed using Western blot, and the morphology and morphometric parameters of the injury site were assessed using transmission electron microscopy (TEM). Nerve compression-injured rats showed no significant difference between resistance-exercised and control rats on either their functional performance, levels of myelin proteins, morphology, or morphometric measurements. On the other hand, in nerve crush injury, the resistance exercise rats performed better in toe spread and extensor postural thrust scores when compared to the injured controls. The TEM revealed that distal segments of crush-injured nerves of the resistance-exercised rats had better morphology compared to those of the crush-injured controls. Our data suggest that resistance exercise prior to a crush injury to sciatic nerve injury led to a better functional recovery, likely through a pro-myelinating effect.